Measuring Public Satisfaction in Public Services: A Simulation Study of Service Elements and IKM Measurement Methods (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Public service quality serves as a crucial metric for assessing how well the government meets the needs and expectations of the community. Within public administration, the effectiveness of public services indicates the government's capability to deliver governance that is open, responsible, and focused on the citizens. In Indonesia, one tool for gauging public service effectiveness is the Community Satisfaction Index (Indeks Kepuasan Masyarakat/IKM). This research seeks to examine how community satisfaction in public services is measured by identifying various service components and the approach used to compute the IKM. A descriptive qualitative research method is employed, utilizing a literature review. Information was gathered from books, academic journals, government regulations, and other scholarly materials relevant to public service quality and community satisfaction. The results reveal that the IKM measurement system offers a comprehensive framework for assessing the performance of public services based on several aspects, including service requirements, processes, completion time, costs, the skills and conduct of service personnel, and available facilities. Additionally, the findings demonstrate that enhancements in service quality, transparency, and the responsiveness of public organizations greatly affect community satisfaction levels. As a result, ongoing assessments of public services through the IKM framework are vital for improving governance effectiveness, boosting service delivery, and reinforcing public confidence in government agencies.